The Leadership of Kiai Ali Maksum in the Poem of Abdullah Bin Nuh - Abdul Wahab Nafan; Rika Nurfadhilah Halim (Tashwirul Afkar, 2022)
Abdullah bin Nuh is an Indonesian scholar with a lot of expertise and work. One of his works is in the field of Literature. One of his literary works is a poem that complements Kiai Ali Maksum Krapyak Yogyakarta. This paper explores the leadership role of Kiai Ali Maksum, which is reflected in Abdullah bin Nuh's poem. This research use the analysis of Bayan studies, furthermore, this study aimed to examine the poem in the domain of language style in the poem. Based on the study's findings, Abdullah bin Nuh described Kiai Ali Maksum as having broad insight, leadership, and discipline. Abdullah bin Nuh's poem includes language styles such as tashbih, kinayah, majaz, and isti'arah.